Hans Vredeman de Vries and his influence: occasioned by a congress (Bulletin KNOB, 2004)
The congress 'Hans Vredeman de Vries and his influence' in early 2004 gave rise to looking at the present state of affairs on this subject on the basis of the latest data on his life and work. It appeared  that (traditionally) there is much more interest in this important, versatile artist outside the Netherlands than in his own country.These past two decades the attention was chiefly focused on classicism, and notably the aesthetic aspects of it, whereas the cultural-historical aspects of the wide North-European movement of mannerism incorporated by Vredeman de Vries was neglected. For this reason a lance is broken for investigating the export of ideas and artists from the Netherlands at the end of the 16th century in an international context and making a start with updating and reassessing our knowledge of our own artists and buildings from the period 1565-1630.